2019
DOI: 10.1128/aac.01745-18
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Resistance to Quinolones and β-Lactam Antibiotics in Enteroaggregative and Enterotoxigenic Escherichia coli Causing Traveler’s Diarrhea

Abstract: The objective of this study was to assess the antimicrobial resistance of enteroaggregative Escherichia coli (EAEC) and enterotoxigenic E. coli (ETEC) strains causing traveler’s diarrhea (TD) and to investigate the molecular characterization of antimicrobial resistance genes to third-generation cephalosporins, cephamycins, and quinolones. Overall, 39 EAEC and 43 ETEC clinical isolates were studied. The susceptibilities of EAEC and ETEC against ampicillin, amoxicillin-clavulanic acid, cefotaxime, imipenem, chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 60 publications
3
40
1
Order By: Relevance
“…In this study, ST131 exhibited increased frequency of resistance to fluoroquinolones and ampicillin-sulbactam compared to ST38, which was often non-susceptible to nitrofurantoin. Increased frequency of fluoroquinolone resistance in ST131 vs. ST38 has been previously described (Alghoribi et al, 2015;Gauthier et al, 2018;Guiral et al, 2019) and is a hallmark of clade C strains. Only 3/41 ST131 isolates in this study were susceptible (S or I) to fluoroquinolones, all of which were clade A.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In this study, ST131 exhibited increased frequency of resistance to fluoroquinolones and ampicillin-sulbactam compared to ST38, which was often non-susceptible to nitrofurantoin. Increased frequency of fluoroquinolone resistance in ST131 vs. ST38 has been previously described (Alghoribi et al, 2015;Gauthier et al, 2018;Guiral et al, 2019) and is a hallmark of clade C strains. Only 3/41 ST131 isolates in this study were susceptible (S or I) to fluoroquinolones, all of which were clade A.…”
Section: Discussionmentioning
confidence: 78%
“…However, hinting that the epidemiology may be changing, the 2016 SENTRY Antimicrobial Surveillance Study demonstrated that the bla CTX-M-27 gene (17.3%) is also significant in E. coli UTI and BSI isolates, compared to the bla CTX-M-15 gene (55.5%; Mendes et al, 2019). Similarly, ST131 carrying the bla CTX-M-27 gene is also a frequent minority around the globe (Livermore et al, 2007;Cao et al, 2011;Dahbi et al, 2013;Matsumura et al, 2013;Seiffert et al, 2013;Roer et al, 2017;Guiral et al, 2019;Peirano and Pitout, 2019;Birgy et al, 2020). The relative advantages of one CTX-M family gene vs. another are not clear, though the bla CTX-M-27 gene may confer additional activity against ceftazidime (Bonnet et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…coli commonly associated with urinary tract infections and bacteremia in humans (Hernandez et al ., 2013; Dolejska and Literak, 2019; Shnaiderman‐Torban et al ., 2020) but also found in wildlife (Alcala et al ., 2016; Guenther et al ., 2017). According to a recent study, the ST38/CTX‐M‐15‐resistant clone was found in a Mongolian wild bird (Guenther et al ., 2017) and the same combination was detected in a human clinical isolate in India (Guiral et al ., 2019). These results are in line with the fact that ST38 lineage is considered an expanded and pandemic clone as well as this lineage appears to be independent of antimicrobial selective pressure in clinical environments (Guenther et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The most well-known member of this family, Escherichia coli , is ubiquitous as an intestinal commensal in humans, but it can act as a diarrheagenic gastrointestinal tract pathogen ( 1 ) or as an extraintestinal pathogen causing urinary tract infections ( 2 ) and sepsis ( 3 ). Common E. coli lineages causing either intestinal or extraintestinal disease are increasingly found to be resistant to multiple drugs ( 4 6 ). Antibiotic resistance in E. coli can arise by mutations in diverse targets or by acquisition of preexisting genes whose products target antibiotics for alteration or efflux ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%